Unilateral left rectus sternalis muscle: a case report - J. P., Jessy; K. V., Amrutha; Abraham, Joseph (International Journal of Research in Medical Sciences, 2017)
The rectus sternalis muscle is a small supernumerary muscle present in the anterior thoracic wall and is superficial to the sterno-costal fibers of pectoralis major muscle. In present study we came across left rectus sternalis, originated as a small tendon from the aponeurosis of the external oblique muscle, and the fascia of the rectus abdominis, and seen inserted into the clavicular fibres of pectoralis major of the opposite side of the manubriosternal joint. The rectus sternalis or sternalis muscle is of much importance in the field of radiology or surgery as its presence and knowledge might be effective and useful for the radiologists and surgeons during management of the pectoral region.